Importance of Interactive Language Input in English Language Teaching in Sports College - Zijun Shen; Yuyu Xue; Yongfei Zhong; Qiong Xu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In Sports Colleges, the role of input in second language acquisition is critical, serving as a structural backbone for the learning process. The typical challenges of English language education—characterized as "time-consuming and fruitless"—are particularly pronounced due to a lack of engaging, sports-related language acquisition scenarios. Traditional teaching methods often fail to incorporate sufficient sports-specific lexical input, crucial for meeting the prerequisites of effective second language learning in this unique educational setting. This study emphasizes the need for interactive language input that integrates sports terminology and scenarios, proposing that such an approach can significantly improve engagement and educational outcomes. By focusing on interactive techniques tailored to the interests and activities of sports students, this approach seeks to create natural, compelling learning environments that enhance both linguistic and athletic training. The paper discusses ways to implement these sports-centered interactive methods to optimize English language acquisition in Sports Colleges.